Pharmacological strategies for preventing post-stroke seizures and epilepsy - Kawamura, Yuki; Trinka, Eugen; Quinn, Terence J.; Emsley, Hedley C. A.; Zelano, Johan; Tanaka, Tomotaka; Ihara, Masafumi; Sansing, Lauren H.; Liebeskind, David S.; Mishra, Nishant K. (Frontiers in Neurology, 2026)
Stroke is the most common cause of new-onset seizures and epilepsy in the older population, which is associated with increased morbidity and mortality. Post-stroke seizures (PSS) are traditionally divided into early and late seizures, occurring before and after 7 days post-stroke, respectively. A single late seizure is sufficient to diagnose post-stroke epilepsy. This narrative review discusses approaches to diagnosing and treating PSS, as well as the various pharmacological agents available. Although current evidence is limited, we suggest that levetiracetam and lamotrigine may be preferred agents for preventing acute seizure recurrence. Statins, GLP-1 agonists, eslicarbazepine, perampanel, and losartan have not been evaluated yet and need further study on their ability to prevent first-time seizures in stroke patients. While clinical trials of antiseizure medications can be costly, further research into biomarkers of epileptogenesis could facilitate more feasible clinical trials to enhance the evidence base for antiseizure medications in post-stroke seizures and epilepsy.